Thiazole: A Privileged Motif in Marine Natural Products - Kumar, Sunil; Aggarwal, Ranjana (Mini-Reviews in Organic Chemistry, 2019)
Marine natural products have proven to be a rich source of drugs and drug leads. These natural products are secondary metabolites and show biological activity against bacteria, fungi and viruses. Natural products containing thiazole ring occur often in marine sources. They exhibit diverse and remarkable biological activities, including antitumor, antibacterial, anti-inflammatory and cytotoxic activities, to name a few. This review surveys the natural thiazole derivatives that have been isolated from marine microorganisms, with emphasis on biological implications in last three decades.
Keywords: secondary metabolite